2008
DOI: 10.1007/s10163-007-0186-9
|View full text |Cite
|
Sign up to set email alerts
|

Application of the WAMED model to landfilling

Abstract: A cost methodology is proposed for evaluating the ecological-economic effi ciency of a municipal solid waste management scheme based on the recommendations of cost-benefi t analysis and the full-cost accounting methodology for municipal solid waste management. The methodology employs the previously introduced waste managements' effi cient decision (WAMED) model and the company statistical business tool for environmental recovery (COSTBUSTER) indicator. A case study presents the practical application of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…They also showed that the investment capital and operating costs for incineration are higher than those for landfilling and concluded that incineration facility becomes competitive financially when the landfill facility is located at a considerable distance from the city (500 km). Moutavtchi et al (2008Moutavtchi et al ( , 2010) developed a cost structure model for solid waste management which included capital costs, operating costs, other costs (that we have also considered in this paper), in addition to this they included costs for extensive and routine repairs, infrastructure costs, investment project services costs, costs for current monetary damage caused by pollution of the environment, environmental taxes. Rhoma et al (2010) developed a mathematical model for estimating solid waste management costs including: logistic costs, vehicle costs, personnel costs, container costs etc.…”
Section: Sensitivity Analysis and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also showed that the investment capital and operating costs for incineration are higher than those for landfilling and concluded that incineration facility becomes competitive financially when the landfill facility is located at a considerable distance from the city (500 km). Moutavtchi et al (2008Moutavtchi et al ( , 2010) developed a cost structure model for solid waste management which included capital costs, operating costs, other costs (that we have also considered in this paper), in addition to this they included costs for extensive and routine repairs, infrastructure costs, investment project services costs, costs for current monetary damage caused by pollution of the environment, environmental taxes. Rhoma et al (2010) developed a mathematical model for estimating solid waste management costs including: logistic costs, vehicle costs, personnel costs, container costs etc.…”
Section: Sensitivity Analysis and Discussionmentioning
confidence: 99%
“…Our model developed in this paper contains some variables and some equations for calculation similar to those presented by Rhoma et al (2010) and Moutavtchi et al (2008Moutavtchi et al ( , 2010. The calculation model developed by us is simple, easy to use, but can be improved by adding the costs of the environmental impact (the costs required to reduce the emissions in the product chain "from cradle to grave" to a sustainable level, costs for sustainable energy sources etc.)…”
Section: Sensitivity Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now a range of CBA's have been performed, particularly comparing incineration with landfilling (Dijkgraaf & Vollebergh 2004;Eshet et al 2005;Moutavtchi et al 2008). A large number of LCA's have also been performed on waste management options (Baky & Eriksson 2003;Cherubini et al 2008;Eriksson et al 2007;Finnveden et al 2007b;Finnveden 1999;Kirkeby et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Waste management solutions -including waste-to-energy (WtE) solutions -have so far primarily been analysed using life cycle assessments (LCA) with a focus on the environmental impact of the different waste management solutions, from the generation to the disposal of waste. Cost-benefit analysis (Dijkgraaf & Vollebergh 2004;Eshet et al 2005;Moutavtchi et al 2008;Tietze-Stockinger et al 2004), multi-criteria decision analysis (El Hanandeh & El-Zein 2009;Longden et al 2007;Morrissey & Browne 2004;Shmelev & Powell 2006) and various other tools, e.g., energy balance analysis (Dornburg & Faaij 2006;Luoranen & Horttanainen 2007;Murphy & McKeogh 2004), have also been applied, albeit to a lesser degree. Alternatives may also be analysed with the use of optimization models, but normally not taking the energy sector into account (Broitman et al 2012;Juul et al 2013;Kan et al 2010).…”
Section: Introductionmentioning
confidence: 99%